HUBUNGAN INISIASI MENYUSU DINI (IMD) TERHADAP SUHU BADAN BAYI BARU LAHIR (BBL) DI BPM FAUZIAH HATTA PALEMBANG TAHUN 2019 - Sagita Darma Sari; Fitri Indriani (STIKES Abdurrahman. Pusat Informasi dan Manajemen, 2021)
Hypothermia is a major cause of morbidity and mortality in newborns at developing countries. The World Health Organizations (WHO) has recommens to maintain heat in newborns care, however hypothermia continues become a normal neonatal condition, which is unidentified, not documented and limited treatment. The purpose of this study was to determine the relationship between IMD and body temperature of newborns in 2019 BPM Fauziah Hatta Palembang. The method uses in this study was to uses descriptive analytical design, collecting samples using accidental sampling totaling 50 people respondent, data was collected by measuring temperature directly after birth and 1 hour after birth using a digital thermometer and recorded in the observation sheet. The results showed a ρ-value of 0,000 <ɑ (0,05) which means there is a significant relationship between the Initiation of Early Breastfeeding Against the Body Temperature of a Newborn. It is expected that the IMD method is implemented by health staffs, particularly midwives in order to assist the improvment of body temperature within the normal of newborns.